Metabolic muscle damage and oxidative stress markers in an America`s Cup yachting crew - Barrios, C.; Hadala, M.; Almansa, I.; Bosch-Morell, F.; Romero, F. J. (Archivos de medicina del deporte, 2008)
The America`s Cup Challenge is the sailing event requiring the highest physiological and conditioning demands. In this study, muscle enzymatic activities involved in tissue damage and a marker of oxidative stress, malondialdehyde (MDA), were monitored in plasma of members of an America`s Cup yachting crew. The preventive benefi ts of allopurinol (a xanthine oxidase inhibitor) on muscle damage were also tested. Methods: Venous blood samples were taken from all 27 members of an America`s Cup yachting crew. In period A, samples were obtained before the start of a 5-days fl eet racing, after the last race (6 races in total), and after the 10 match races (8 days) corresponding to the 1st round of the 2007 Louis Vuiton`s Cup. In period B, samples were collected just after the 2nd round of the Louis Vuiton`s Cup (7 match races). In period B, crew members were randomly divided into 2 groups. One group (13 participants) received 300 mg/day of allopurinol (an inhibitor of xanthine oxidase), 3 hours before racing. The other 10-members group received placebo. Four sailors did not participate in this racing phase. Results: All participants showed an increase in CK (46%, from 262.4 to 383.7 U/L, p<0.01), and AST (37.6%, from 27.2 to 37.4 U/L, p<0.05) activities in plasma both after the fl eet and match races of period A. Grinders present maximal increases in CK activity (up to 80%). In period B, signifi cant decreases in both plasma CK (from 445.8 to 333.6 U/L, p<0.05) and AST (36.3 to 31.1 U/L, p<0.05) activities appeared among participants receiving allopurinol. At the end of period A, plasma MDA levels were higher in all participants as compared to non-participant athletes (1.54 vs 1.18 nmol/mL, respectively, p<0.05). A statistically signifi cant decrease (37,5%) in plasma MDA (from 1.55 to 1.03 nmol/mL, p<0.05) occurred in sailors treated with allopurinol during period B. Placebo group showed no change. Conclusions: America`s Cup is a sailing sport modality that increases muscle damage markers after races. Xanthine oxidase, a free radical-generating enzyme, seems to be implicated in the tissue damage occurring after this exhaustive exercise, in view of the effect of allopurinol.